2013
DOI: 10.1002/adhm.201200385
|View full text |Cite
|
Sign up to set email alerts
|

A Polymer–(Tandem Drugs) Conjugate for Enhanced Cancer Treatment

Abstract: A novel strategy for combination chemotherapy (platinum and demethylcantharidin) via a polymer-(tandem drugs) conjugate for enhanced cancer treatment is demonstrated. Cisplatin can be released inside cell by reduction to attack DNA, while DMC will be hydrolyzed subsequently to block DNA-damage-induced defense mechanisms by serine/threonine phosphatase PP2A inhibition. Synergistic effect of the polymer-(tandem drugs) conjugate causes complete suppression of H22 liver tumor xenografts without recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 37 publications
0
39
0
Order By: Relevance
“…Recently, demethylcantharidin (DMC), as protein phosphatase 2A (PP2A) inhibitor, showed enhanced antitumor activity with DNA‐damaging agents by specifically inhibition of PP2A without evident acute or chronic toxicity . Previous studies have shown that combination use of cisplatin and DMC could synergize cancer therapy …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, demethylcantharidin (DMC), as protein phosphatase 2A (PP2A) inhibitor, showed enhanced antitumor activity with DNA‐damaging agents by specifically inhibition of PP2A without evident acute or chronic toxicity . Previous studies have shown that combination use of cisplatin and DMC could synergize cancer therapy …”
Section: Methodsmentioning
confidence: 99%
“…The key features in DDBSP and DD‐NP include: (i) Dual synergistic drugs were combined at a fixed and precise ratio in DD‐NP for precise nanomedicine with extraordinary high drug loading that can hardly be achieved in other delivery systems via conventional drug conjugation/encapsulation. (ii) The backbone‐type polymer was site‐specifically chain‐shattered via reduction of Pt(IV) to Pt(II) and acidolysis of DMC‐containing β‐carboxylic amide to DMC in the endosomal/lysosomal reductive and acidic microenvironments, making the drug release in a controlled but triggered manner . (iii) The exceptional high content of Pt heavy metals in the polymer chain assures possible monitoring of the spatial/temporal dynamic distribution as well as metabolism of NPs via Pt‐based drug‐mediated computer tomography (DMCT).…”
Section: Methodsmentioning
confidence: 99%
“…Compared to cisplatin, Pt (IV) complexes are more inert, but there are still some limitations, such as instability in blood, rapid removal by kidney, and wide distribution in normal tissues . It is desired that most of Pt (IV) complexes are reduced to Pt (II) complexes within tumor cells.…”
Section: Platinum (Iv) Complex‐based Delivery Systemsmentioning
confidence: 99%
“…Compared to cisplatin, Pt (IV) complexes are more inert, but there are still some limitations, such as instability in blood, rapid removal by kidney, and wide distribution in normal tissues. 125,126 It is desired that most of Pt (IV) complexes are reduced to Pt (II) complexes within tumor cells. However, once Pt (IV) complexes entered the blood, most of them were irreversibly bound to plasma proteins and the effective therapeutical dosage was reduced.…”
Section: Pt (Iv) Complexes Coupled To Nanocarriersmentioning
confidence: 99%
“…93 The nano-sized conjugate exhibited superior activity and safety over the free drugs in mice bearing orthotopic mammary adenocarcinomas. An interesting example of this strategy is provided by Zhou et al 94 Rather than conjugating the two drugs—cisplatin (CIS) and demethylcantharidin (DMC)—to individual sites on the polymer chain, they took advantage of the redox activity of Pt to oxidise the four-coordinate Pt(II) to six-coordinate Pt(IV) and then complex it with DMC. This tandem drug complex, Z-DMC-CIS, was then conjugated to a PEG- b -P(LA- co -MCC/OH) copolymer via the DMC’s second carboxylate group, creating a PDC that assembled through nanoprecipitation into micelles 200–240 nm in diameter.…”
Section: Macromolecular Sapdsmentioning
confidence: 99%